Growing up with jazz : twenty-four musicians talk about their lives and careers - Stokes, W. Royal (Oxford University Press, 2005)
Focusing on how these figures became jazz musicians, this volume discusses the two most prominent US jazz musicians: the influential bop drummer Art Blakely and the famous jazz pianist and personality Dr Billy Taylor.
Includes index.
Keywords: Jazz musicians -- Interviews.; Musiciens de jazz -- Entretiens.; MUSIC -- Genres & Styles -- Jazz.; Jazz musicians; Interviews